Influences of different sedatives on gastric antrum contraction in patients with acute brain injury - Mei, Meihua; Yao, Mingli; Li, Jingchao; Qiu, Chunfang; Wang, Yufang; Li, Yan; Shi, Lei; Wang, Lingyan; Ouyang, Bin (Frontiers in Neurology, 2024)
BackgroundPatients with acute brain injury (ABI) often exhibit gastrointestinal motility disorder and the administration of sedatives may exacerbate the gastrointestinal dysfunction. This study aims to evaluate the influences of different sedatives on gastric antrum contraction in patients with acute brain injury (ABI).MethodsA prospective observational study was performed in 37 adult ICU patients with ABI, and 18 adult healthy volunteers were recruited as normal controls. Gastric motility, including frequency (ACF), amplitude (ACA), and motility index (MI), was measured with ultrasound before and after using sedatives, either propofol (Group A), midazolam (Group B), or dexmedetomidine (Group C). The influences of different sedatives on gastric motility were analyzed.ResultsAll patients with acute brain injury (n = 37) exhibited decreased ACF and MI compared with those in healthy control (n = 18) (ACF: 2.41 ± 0.89 times/2 min in ABI vs. 4.5 ± 0.39 times/2 min in control, MI: 1.25 ± 0.57 in ABI vs. 3.59 ± 0.24 in control, p = 0.001). All sedatives, either propofol, midazolam, or dexmedetomidine, had inhibited effects on gastric motilities [In Group A (n = 13), 1.14(0.59, 1.44) before vs. 0.84(0.09, 0.83) after, p = 0.002; In group B (n = 12), 1.48(0.73, 1.62) before vs. 0.31(0.04, 0.58) after, p = 0.007; In Group C (n = 12), 2.74(1.70, 3.01) before vs. 1.39(0.70, 2.28)]. However, dexmedetomidine showed significantly less inhibition either on ACA or MI compared with propofol and midazolam (ACA 20.67 ± 33.59% in dexmedetomidine, 51.50 ± 32.83% in propofol, 60.43 ± 22.40% in midazolam, p = 0.002; MI 36.00 ± 34.77% in dexmedetomidine, 60.69 ± 27.49% in propofol, 68.81 ± 20.84% in midazolam, p = 0.012).ConclusionPatients with ABI exhibited decreased gastric motility. All sedatives, either propofol, midazolam, or dexmedetomidine, had inhibited effects on gastric motilities. Dexmedetomidine has less inhibitory effects on ACA and MI compared with propofol and midazolam.